Direct arylation for the synthesis of 2-arylquinolines from N-methoxyquinoline-1-ium tetrafluoroborate salts and arylboronic acids. Issue 11 (14th March 2018) - Ren, Xiaoxiao; Han, Shuaijun; Gao, Xianying; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Graphical abstract: Highlights: Using derect C–H functionalization to prepare 2-arylquinolines. The system features good substrates tolerance with high regioselectivity. The rapid reaction proceeds under an ambient temperature under air atmosphere. Abstract: A rapid and direct arylation reaction of N -methoxyquinoline-1-ium tetrafluoroborate derivatives and arylboronic acids with high regioselectivety at room temperature was discovered. The reaction shows exceptional functional group tolerance and broad substrate scope regarding both the quinoline derivatives and the arylboronic acids.